Dynamics of Employee Engagement and Implementation of Adaptive Leadership in Increasing Work Productivity: The Mediating Role of Job Satisfaction - Sjahruddin, Herman; Sari, Desi Permata; Hakiki, Ridwan (Jurnal Informatika Ekonomi Bisnis, 2024)
This study investigates the intricate dynamics of employee engagement, adaptive leadership, job satisfaction, and work productivity within the organizational context of PT Gangking Raya office in Makassar. Through a sample of 47 individuals, the study employs a rigorous analysis using SmartPLS to examine both direct and indirect relationships among these key variables. The results indicate a significant positive impact of employee engagement on job satisfaction and work productivity, emphasizing the pivotal role of an engaged workforce. While adaptive leadership shows a positive association with job satisfaction, its direct influence on work productivity is not statistically significant. Notably, job satisfaction emerges as a significant mediator between both employee engagement and adaptive leadership with work productivity. This suggests that cultivating high job satisfaction levels is crucial in maximizing the positive outcomes of employee engagement and adaptive leadership on overall work productivity. These findings offer valuable insights for organizational strategies, underscoring the importance of fostering employee engagement, adaptive leadership practices, and job satisfaction for a thriving and productive workplace environment at PT Gangking Raya.